2021
DOI: 10.1016/j.bjps.2021.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Reconstructive Microsurgery in the Elderly Population: a Multicentric Prospective Study

Abstract: Background: Safety of reconstructive microsurgery in elderly patients is still a topic of debate, because no conclusive evidence exists that provides indications and risk evaluation in elderly patients. The purpose of this study, which the Italian Society for Plastic, Reconstructive, and Aesthetic Surgery (SICPRE) has promoted, is to evaluate the safety and the complication risk of elective reconstructive microsurgery in elderly patients as well as to identify patient-or procedurerelated risk factors. The seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…However, it is also a highly subjective assessment by the anesthesiologist, as several studies showed significantly weak inter-rater reliability [ 35 ]. Even when other parameters, such as the G8 score, are used to define frailty as a parameter for postoperative mortality, morbidity, and prolonged recovery, no significant differences could be demonstrated in the assessment of these values compared with the ASA score [ 36 ]. As shown in our study but also in other studies, free flap transfer per se is no longer a contraindication for elderly or very old patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also a highly subjective assessment by the anesthesiologist, as several studies showed significantly weak inter-rater reliability [ 35 ]. Even when other parameters, such as the G8 score, are used to define frailty as a parameter for postoperative mortality, morbidity, and prolonged recovery, no significant differences could be demonstrated in the assessment of these values compared with the ASA score [ 36 ]. As shown in our study but also in other studies, free flap transfer per se is no longer a contraindication for elderly or very old patients.…”
Section: Discussionmentioning
confidence: 99%
“…Age was not considered a contraindication. (Cordova et al, 2021; Laporta, Sorotos, et al, 2017) Frail patients with an ASA score above III and/or with a contraindication for abdominal free flaps (i.e., previous abdominal surgeries, low body mass index [BMI], insufficient donor tissues) received different reconstructive options and were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%